Knowledge and practice on breastfeeding and infant feeding practices in pregnant women, at Sarjapura, Bangalore - C., Pradeep; S., Hemavarneshwari (International Journal Of Community Medicine And Public Health, 2017)
Background: Breastfeeding is the unique source of nutrition that plays an important role in the growth, development and survival of infants. Breast feeding is important, particularly in developing countries because of its relationship with child health and birth spacing. The frequency of breast feeding also plays a role in lactational amenorrhea. Though breast feeding is universal in India, the rate of initiation, exclusive breastfeeding and timing of complementary feeds are far from desirable. Methods:A cross sectional study was carried out in Sarjapura, Bangalore from September 2010 to May 2011. Using stratified random sampling method a sample of 118 pregnant mothers who were in 3rd trimester included in this study. Their knowledge and practice with regard to prelacteal feeds, initiation of breastfeeding, feeding colostrum, exclusive breastfeeding and age of introduction of complementary feeds were assessed by interviewing using pre-tested semi structured questionnaire. Results: The prevalence of mothers giving prelacteal feeds, initiation of breastfeeding within half an hour after delivery, exclusive breastfeeding at 6 months and age of introduction of complementary feeds after 6 months were 97.4%, 28%, 25.4% and 25.4% respectively. Conclusions:There is a need for educational interventional to promote the breastfeeding and infant feeding practices in the community.